The Training in Educational Assessment practices of Special Education Teachers - Javier J. Maquilón Sánchez; María José Martínez Segura; Mari Paz García Sanz; Francisco Alberto García Sánchez (Revista Electrónica Interuniversitaria de Formación del Profesorado)
Admitting the importance of evaluation in the culture of quality, and especially in the field of education, 233 teachers have taken part in this research. They work to help children with especial educational needs, in Murcia (Spain).We asked them about their level of real execution of practical assessment of learning, teaching and programs, and the level of importance that they give to this evaluation. In this study we analyzed the differences found in variables as gender, type of the school (specific/ordinary), speciality (therapeutic pedagogy/audition and language), administrative situation (official/supply teacher) and years of experience. In general, they gave more importance to evaluation than their real practice shows, and it concerned more the evaluation of learning and less that of teaching. The comparison between variables is allowed to make an x-ray about commitment to practical systematized assessment.